2006
DOI: 10.1002/ijc.22344
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of genetic variation in the IGF1 gene and risk of prostate cancer

Abstract: Insulin-like growth factor-I (IGF1) stimulates cell proliferation, decreases apoptosis, and has been implicated in cancer development. Epidemiological studies have shown elevated levels of circulating IGF1 to be associated with increased risk of prostate cancer. To what extent genetic variation in the IGF1 gene is related to prostate cancer risk is largely unknown. We performed a comprehensive haplotype tagging (HT) assessment of single nucleotide polymorphisms (SNPs) representing the common haplotype variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Prospective studies have shown elevated levels of circulating IGF-I to be associated with several cancer types, including prostate cancer (4)(5)(6). Genetic variation in the IGF1 gene seems to play a role in determining circulating levels (7,8,9) and may also influence prostate cancer risk (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have shown elevated levels of circulating IGF-I to be associated with several cancer types, including prostate cancer (4)(5)(6). Genetic variation in the IGF1 gene seems to play a role in determining circulating levels (7,8,9) and may also influence prostate cancer risk (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, increasing circulating levels of IGFI conferred a clear trend toward increased risk of prostate cancer. In addition, we recently identified several variants in the 3 ¶ region of the IGF1 gene associated with both increased prostate risk as well as elevated circulating IGFI levels, a finding supporting the role of IGFI in prostate cancer etiology along the lines of Mendelian randomization (12). SST seems to result in suppressed levels of both IGFI and GH1 (13).…”
Section: Introductionmentioning
confidence: 64%
“…Although the IGF1 and IGFBP3 genes are the most obvious candidates to account for this variability (12,21), other members of the growth hormone/IGFI axis are also candidates to influence circulating IGFI and IGFBP3 hormone levels. In the present study, we report a missense SNP in the SSTR5 gene associated with a decrease in plasma levels of IGFBP3 by 11% per rare allele as confirmed in an independent study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations